PENGARUH ECONOMIC VALUE ADDED (EVA), RETURN ON ASSET (ROA) DAN TOTAL ARUS KAS TERHADAP PRICE BOOK VALUE (PBV) PADA PERUSAHAAN PROPERTY, REAL ESTATE DAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2016 - Jasmine, Jasmine; Rukmana Sari, Ike; Govandy Lie Jaya, Leo; Suwandy, Suwandy (Aksara Public, 2018)
Researcher used quantitative research approach. The kind of this study is causality relationship and explanation. Population of the study consist of 65 Property, Real Estate and construction companies on registered at Indonesia stock exchange (BEI). Sampling of this study were amount 186 of financial statement come from Property, Real Estate and Construction companies registered at Indonesia Stock Exchange on the year of 2011-2016. Colleting data technique is documentation study. Analysis uses multiple linear programming model. The study result’s shows that Economic Value Added (EVA) partially no effect and not significant to Price Book Value (PBV) on property, real estate and construction companies registered at Indonesia Stock Exchange (BEI) on the year 2011-2016. Return on Asset (ROA) partially effects and significant to Price Book Value (PBV) on property, real estate and construction companies registerd at Indonesia Stock Exchange (BEI) on the year tahun 2011-2016. Total Cash Flow partially effects and significant to Price Book Value (PBV) on property, real estate and construction companies registered on Indonesia Stock Exchange (BEI) on the year 2011-2016. Economic Value Added (EVA), Return on Asset (ROA) and total cash flow simultaneously effects and significant to Price Book Value (PBV) on property, real estate and construction companies registered at Indonesia Stock Exchange (BEI) on the year 2011-2016.